Determinants of Poverty in West Java Province After the Regional Expansion of Pangandaran District - M. Yusril Fiskal; Dyah Titis Kusuma Wardani (Journal of Economics Research and Social Sciences, 2020)
This research aims to analyze the influence of Human Development Index, population growth, and Gross Regional Domestic Product on poverty level in 27 districts/cities in West Java Province. The panel data obtain from Statistics Indonesia, consists of time series data is taken from 2015 to 2018, and cross-section data includes 27 districts/cities in West Java Province. The estimator of this research is using multiple linear regressions (Ordinary Least Squares) with fixed-effect model. The results show that Human Development Index, population growth and Gross Regional Domestic Product have negative and significant effect on the poverty level in West Java Province after regional expansion of Pangandran district.